Accuracy Evaluation Activities Tc-99m in Single Organ and All Organ using Gamma Camera Mediso AnyScan Dual Head S and Anthropomorphic Phantom - Diah Shanti Utaminingtyas; Johan A. E. Noor; Nur Rahmah Hidayati (Natural B, Journal of Health and Environmental Sciences, 2016)
In term of nuclear medical, Radiopharmaceuticals with Tc - 99m radioisotope for kidney examination inserted into the body will emit gamma radiation that can be detected by a gamma camera. Gamma camera will display the distribution of radioisotopes in the patient's body and measure examined organ function in the form of image. A committee in nuclear medical developed Medical Internal Radiation Dosimetry (MIRD) method, the standard method on the way calculating activities in organ by image quantification. Differences in the activity of Tc-99m were measured by a dose calibrator with detected activity of organs to determine the accuracy of activity measurement. These results indicated that detected activity in the organ, calculated by the method MIRD, were smaller than the calibrator measurement result. The differences percentage in the activity of a single organ (counting each organ), involving all organs (enumeration simultaneously including kidney, bladder, heart and liver), has value <20% that indicate the reliability of MIRD method to use in internal dosimetry.